Innovation-based regional structural change: Theoretical reflections, empirical findings and political implications - Knut Koschatzky (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2018)
The objective of this paper is to broaden the knowledge base on the topic of innovation-based regional structural change and to discuss the possibilities of raising structurally weak regions to a dynamic growth path by means of innovation-promoting measures. The background to this objective are political developments in Germany with regard to the development of a comprehensive German support system for structurally weak regions from 2020 onwards. While regional structural support (ERDF and German regional support) is so far essentially concentrated on regions in the eastern federal states, it should focus in future on structurally weak regions in all federal states and eliminate the differentiation between eastern and western Germany (Deutscher Bundestag 2016, 4). The experience gained in the eastern German states with the focus on innovation as a driver of structural change is intended to provide a starting point here, but taking into account the fact that some structural factors differ markedly between East German and West German regions. Against this background, this paper focuses on the innovation policy component of a system for promoting structural change in structurally weak regions.
urn:nbn:de:0011-n-4903761
Keywords: 330